Nilai Ekonomi Karkas dan Non-Karkas Sapi Bali Betina Afkir pada Berbagai Kelompok Umur - Banamtuan, Sefrans; Jelantik, I Gusti; Krova, Maria (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2025)
This study aimed to analyze the economic value of cull female Bali cattle at different ages in Kupang Regency. A total of 40 cows were grouped into young (2-4 years), medium (4–7 years), and old (7–10 years). Economic parameters measured included live animal value, carcass value, non-carcass value, and added value using the Hayami method. Data were analyzed using ANOVA followed by Duncan’s test. The results showed that age significantly affected the proportion of non-carcass components (P<0.05), but not slaughter weight and carcass percentage. However, the economic value of live animals, carcass, non-carcass, and slaughtering added value increased with age. Older cows generated higher economic returns, although carcass efficiency was relatively constant across age groups. It can be concluded that culling age influences economic value, and the carcass-based selling system (carcass weight) provides more accurate and profitable returns than live weight transactions.